SABUN GEL “AVERLIM” : INOVASI PEMANFAATAN BUAH BELIMBING WULUH (Averrhoa bilimbi L.) SEBAGAI ZAT AKTIF ALAMI DENGAN PENGGUNAAN GELATIN HALAL DARI LIMBAH TULANG AYAM SEBAGAI GELLING AGENT - St. Maryam; Rahmawati; Herman, Hendra (Akademi Farmasi Yamasi Makassar, 2023)
Paddinging Village is one of six villages in Sanrobone District, Takalar Regency. The targets of service in Paddinging village are PKK members. Currently, clean living is being promoted. One effort that can be made to help the village government is to provide training to PKK members to be able to make or produce their own hand washing soap which can be used to clean hands from germs after defecating or after carrying out other activities that require hand hygiene. The aim of this activity is to help the village government provide training to PKK members to be able to make hand washing soap which is used to clean hands from germs after carrying out daily activities. The method consists of providing training and making soap which has been formulated using the natural active ingredients of Averrhoa bilimbi as the basic active ingredient (antiseptic) which is processed into a hygiene product, namely hand washing soap. The result of this activity is that it provides great benefits to the community, especially PKK women, because they can make their own hand washing soap which is safe for health and does not irritate the skin. The formula for the soap provided uses natural active ingredients from Averrhoa bilimbi using halal gelatin from chicken bone waste. This soap can be used directly and can protect yourself and your family by getting into the habit of washing your hands using the soap that has been made.